2013
DOI: 10.1155/2013/753150
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Prevalence, Awareness, Treatment, and Control of Diabetes Mellitus in Mainland China from 1979 to 2012

Abstract: Diabetes mellitus (DM) is one of the primary causes of premature death and disability worldwide. We performed a systematic review and meta-analysis of the published literature regarding the trends in prevalence, awareness, treatment, and control of diabetes mellitus in mainland China. PUBMED, EMBASE, Chinese Biomedical Database, China National Infrastructure database, Chinese Wan Fang database, and Chongqing VIP database were searched. Fifty-six eligible studies were included. Increasing trends in the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
90
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 42 publications
7
90
3
1
Order By: Relevance
“…A meta-analysis of 15 studies in Japan reported no increase in diabetes prevalence, 28 as observed in our analysis. Several recent reports have also documented similar increases in diabetes prevalence to those observed in our analysis in China,29, 30 India,31, 32, 33, 34 Iran, 35 Turkey, 36 and Saudi Arabia 37 . Finally, our finding of the slower rise in diabetes prevalence in women compared with men is consistent with historical data in a few high-income countries 18, 19…”
Section: Discussionsupporting
confidence: 92%
“…A meta-analysis of 15 studies in Japan reported no increase in diabetes prevalence, 28 as observed in our analysis. Several recent reports have also documented similar increases in diabetes prevalence to those observed in our analysis in China,29, 30 India,31, 32, 33, 34 Iran, 35 Turkey, 36 and Saudi Arabia 37 . Finally, our finding of the slower rise in diabetes prevalence in women compared with men is consistent with historical data in a few high-income countries 18, 19…”
Section: Discussionsupporting
confidence: 92%
“…Although poor glycemic control has been associated with greater diabetes‐related health care costs (Degli Esposti et al ., 2013), several studies in different settings have reported suboptimal glycemic control rates among T2D patients (Hu et al ., 2008; McDonald et al ., 2009; Li et al ., 2013). Moreover, a decrease in adequate glycemic control rates has been also observed during past years in some locations (Koro et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated substantial geographic variations and changes in the prevalence of diabetes in China over time, representing a key public health challenge [1][2][3][4][5]. In 2002 National Nutrition Survey, the prevalence of diabetes in adults was only 2.7 % [6], and in 2010 Chronic Disease Risk Factor Surveillance in China, the prevalence had increased to 9.7 % according to the same criteria [7].…”
Section: Introductionmentioning
confidence: 99%